2021
DOI: 10.3390/ijerph181910163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Clay on Phaeocystis globosa Growth and Colony Formation

Abstract: Phaeocystis globosa is a globally distributed harmful algal blooms (HABs) species dominated by the colonial morphotype, which presents dramatic environmental hazards and poses a threat to human health. Modified clay (MC) can effectively flocculate HAB organisms and prevent their subsequent growth, but the effects of MC on colony-dominated P. globosa blooms remain uncertain. In this paper, a series of removal and incubation experiments were conducted to investigate the growth, colony formation and colony develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(98 reference statements)
1
3
0
Order By: Relevance
“…In group 2, broken cells suffered a large area of membrane depression and rupture, while, in group 3, the broken cells burst, and the cytoplasmic contents flowed out through pores in the cell membrane. In both group 2 and group 3, nearly all the residual cell peripheries became clear, illustrating that NC and MC can decrease EPS, in accordance with the report by Ren et al [37]. It should be noted that A. anophagefferens does not have a cell wall, and the EPS sheath is an important barrier.…”
Section: Changes In Cell Shape and Size Of Residual A Anophagefferenssupporting
confidence: 89%
“…In group 2, broken cells suffered a large area of membrane depression and rupture, while, in group 3, the broken cells burst, and the cytoplasmic contents flowed out through pores in the cell membrane. In both group 2 and group 3, nearly all the residual cell peripheries became clear, illustrating that NC and MC can decrease EPS, in accordance with the report by Ren et al [37]. It should be noted that A. anophagefferens does not have a cell wall, and the EPS sheath is an important barrier.…”
Section: Changes In Cell Shape and Size Of Residual A Anophagefferenssupporting
confidence: 89%
“…80% within 3 min of exposure [21] Xanthane and calcium ydroxide modi ed clays, soils, and sands) Amphidinium carterae 83-89% within 30 min of exposure [22] Modi ed soil using amphoteric starch (AS) and poly-aluminium chloride (PAC)…”
Section: Mitigation Of Alexandrium Minutummentioning
confidence: 99%
“…The digital microscopic images showed that the algae cells attached to the CHT/SiO 2 /Gly ruptured (Fig 8(a)), whereas the algae cells on the CHT/SiO 2 /GPTEOS lm remained intact. Since NH 2 group of chitosan is preserved in CH/SiO 2 / Gly, the positively charged amine groups in the chitosan structure could induce stress to the algal cells and promotes cell rupturing [21,52]. Whereas in CHT/SiO 2 /GPTEOS lm, most of the NH 2 of chitosan is used up during the crosslinking process, hence further reducing the electrostatic charge and prevented the algae cells from rupturing.…”
Section: Mitigation Of Alexandrium Minutummentioning
confidence: 99%
See 1 more Smart Citation